SeerahBot: An Arabic Chatbot About Prophet’s Biography (International Journal of Innovative Research in Computer Science & Technology, 2021)
Chatbots have become very popular in our  times and are used in several fields. The emergence of  chatbots has created a new way of communicating between  human and computer interaction. In this study, we have  developed a Chatbot in Arabic language, which is a program  that can understand and analyze Arabic language. The  Chatbot developed in this study contributes to its users about  the Prophet’s biography and provide them with valuable  information. SeerahBot will be the first chatbot dedicated to  the Prophet’s biography. We implemented this system by  using two methods first build retrieval based chatbot from  scratch using natural language processing NLP and machine  learning techniques and second technique we used a chatbot  design platform. To facilitate access to SeerahBot, we have  made it available on Telegram. SeerahBot was tested, and the  results were acceptable.
Keywords: Artificial intelligence; NLP; Arabic chatbot